Pelindungan Konsumen Atas Perjanjian Jual Beli Melalui Smart Contract Dalam Perdagangan Elektronik Melalui Sosial Media - Satriojati, Bima (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2024)
As consequence of developing technology, sell and purchase transactions can be carried out boldly by utilizing the available platforms. Currently, buying and selling in electronic commerce is not only done on marketplace platforms, but also on social media platforms. Apart from that, sell and purchase transaction, which is basically an agreement, is currently developing with the implementation of smart contracts. The implementation of smart contracts in buying and selling transactions via social media raises attention to the position of buyers who generally often do not benefit because of the irregularity between sellers and buyers. Therefore, there are numerous aspects of consumer protection that must be considered, such as advertising of product, standard clauses, and use of personal data